2015
DOI: 10.1007/s12161-015-0221-8
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Detection with MnO2-Modified GCPE

Abstract: In this study, manganese(IV) oxide (MnO 2 ) nanoparticle (np)-modified glassy carbon paste electrode is used for ascorbic acid (AA) detection in fruit juice samples. The experimental parameters like MnO 2 np amount and pH were optimized by using modified full factorial design model. By means of this model, the number of experiments has been reduced. Under optimal conditions, the linear range for AA was obtained between 2.64×10 −6 and −1.5×10 −3 M. Limit of detection (LOD) (3 s/m) and relative standard deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Ç evik et al and Luo et al also reported that the use of MnO 2 np provides better sensitivity compared to bare electrodes for ascorbic acid detection and for glucose biosensors. 15,19 Overall, in the above studies, it has been demonstrated that the better results obtained were due to MnO 2 np introduced in the electrodes' structures. 15,19 On the other hand, the GOx/Al 2 O 3 -TiO 2 /GCPE bioanode exhibited lower maximum current and power densities compared to the GOx/MnO 2 np/GCPE bioanode.…”
Section: Electrochemical Characterization Of the Developed Bioanodesmentioning
confidence: 76%
See 2 more Smart Citations
“…Ç evik et al and Luo et al also reported that the use of MnO 2 np provides better sensitivity compared to bare electrodes for ascorbic acid detection and for glucose biosensors. 15,19 Overall, in the above studies, it has been demonstrated that the better results obtained were due to MnO 2 np introduced in the electrodes' structures. 15,19 On the other hand, the GOx/Al 2 O 3 -TiO 2 /GCPE bioanode exhibited lower maximum current and power densities compared to the GOx/MnO 2 np/GCPE bioanode.…”
Section: Electrochemical Characterization Of the Developed Bioanodesmentioning
confidence: 76%
“…15,19 Overall, in the above studies, it has been demonstrated that the better results obtained were due to MnO 2 np introduced in the electrodes' structures. 15,19 On the other hand, the GOx/Al 2 O 3 -TiO 2 /GCPE bioanode exhibited lower maximum current and power densities compared to the GOx/MnO 2 np/GCPE bioanode. If the GOx/GCPE bioanode's performance is compared with that of the GOx/Al 2 O 3 -TiO 2 /GCPE bioanode, it can be seen that the GOx/Al 2 O 3 -TiO 2 /GCPE bioanode showed better power density but lower maximum current density and OCP values ( Table 2).…”
Section: Electrochemical Characterization Of the Developed Bioanodesmentioning
confidence: 76%
See 1 more Smart Citation
“…For instance, two different studies are carried out while completely covering the available range of AA presents in human bodies. The claimed detection limit of sensor structures is also good, but there is no discussion about the sensitivity of sensor probes [8,39]. Similarly, two different sensor structures based on colorimetric schemes are also claiming the better detection limit to detect the presence of AA.…”
Section: Performance Study Of the Proposed Sensormentioning
confidence: 99%
“…The malnutrition of AA in the human body is closely related to severe symptoms such as scurvy, Parkinson's, Alzheimer's, and cardiovascular diseases [5,6]. Therefore, for the detection of AA, several methods have been proposed including electrochemistry [7,8], fluorescence [9,10], calorimetry [11], liquid chromatography [12], and ultraviolet-visible (UV-vis) spectrometry [13]. However, these methods are not very attractive because of their low sensitivity, limited selectivity, and complicated procedures.…”
Section: Introductionmentioning
confidence: 99%